Investigating the Future in Ureteral Stent Biomaterials and Design: A Review - Salih, Halah Hadi; Kadim, Nabeel; Jawad, Hayder Ismael (Al-Nahrain Journal for Engineering Sciences, 2024)
In today's world, Urinary Tract disorders such as obstructions whatever the causes (stricture, stones), are prevalent and can be extremely dangerous and painful for individuals. One of the most important instruments in the Urological sector for a variety of clinical diseases is the Ureteral stent, a minimally invasive surgical tool for relieving blockages and facilitating kidney-to-Bladder drainage.     This review addressed the problems of biofilm formation and polymers currently available for use as new biomaterials in new Ureteral stent designs, providing a comprehensive update on recent developments in stent development. It also evaluated the various biomaterials that found application as Ureteral stents in relation to various issues such as encrustation, bacterial colonization, urinary tract infections, and related clinical issues. This study concluded with a discussion of biomaterials' potential applications and the design in the Urinary Tract.